Respiration-controlled radiotherapy in lung cancer: Systematic evaluation of the optimal application practice. (May 2023) - Guberina, M.; Santiago, A.; Pöttgen, C.; Indenkämpen, F.; Lübcke, W.; Qamhiyeh, S.; Gauler, T.; Hoffmann, C.; Guberina, N.; Stuschke, M.
Highlights: The benefit of deep inspiration-breath-hold (DIBH) in radiotherapy is demonstrated in a reduced mean lung dose, mean heart dose and lungV20 in comparison to FB-EH for upper lobe lung tumours. For lower lobe lung tumours no relevant differences in lung or heart exposure were observed. Favorable and robust breathing phase of the respiratory cycle for radiotherapy of lower lobe lung tumours: Free shallow breathing, prospectively gated in expiration (FB-EH). Continuously controlled irradiation by online recording of the respiration: The probability of intra-fractional verifications with diaphragm cupola deviations >5 mm was slightly higher for DIBH than for FB-EH exercise. Abstract: Background and purpose: Definitive radiochemotherapy (RCT) for non-small cell lung cancer (NSCLC) in UICC/TNM I–IVA (singular, oligometastatic) is one of the treatment methods with a potentially curative concept. However, tumour respiratory motion during RT requires exact pre-planning. There are various techniques of motion management like creating internal target volume (ITV), gating, inspiration breath–hold and tracking. The primary goal is to cover the PTV with the prescribed dose while at the same time maximizing dose reduction of surrounding normal tissues (organs at risk, OAR). In this study, two standardized online breath–controlled application techniques used alternately in our department are compared with respect to lung and heart dose. Materials and methods: Twenty-four patients who were indicated for thoracic RT received planning CTs in voluntary deep inspiration breath-hold (DIBH) and in free shallow breathing, prospectively gated in expiration (FB-EH). A respiratory gating system by Varian (Real-time Position Management, RPM) was used for monitoring. OAR, GTV, CTV and PTV were contoured on both planning CTs. The PTV margin to the CTV was 5 mm in the axial and 6–8 mm in the cranio-caudal direction. The consistency of the contours was checked by elastic deformation (Varian Eclipse Version 15.5). RT plans were generated and compared in both breathing positions using the same technique, IMRT over fixed irradiation directions or VMAT. The patients were treated in a prospective registry study with the approval of the local ethics committee. Results: The PTV in expiration (FB-EH) was on average significantly smaller than the PTV in inspiration (DIBH): for tumours in the lower lobe (LL) 431.5 vs. 477.6 ml (Wilcoxon test for connected samples; p = 0.004), in the upper lobe (UL) 659.5 vs. 686.8 ml ( p = 0.005). The intra-patient comparison of plans in DIBH and FB-EH showed superiority of DIBH for UL-tumours and equality of DIBH and FB-EH for LL-tumours. The dose for OAR in UL-tumours was lower in DIBH than in FB-EH (mean lung dose p = 0.011; lungV20, p = 0.002; mean heart dose p = 0.016). The plans for LL-tumours in FB-EH showed no difference in OAR compared to DIBH (mean lung dose p = 0.683; V20Gy p = 0.33; mean heart dose p = 0.929). The RT setting was controlled online for each fraction and was robustly reproducible in FB-EH. Conclusion: RT plans for treating lung tumours implemented depend on the reproducibility of the DIBH and advantages of the respiratory situation with respect to OAR. The primary tumour localization in UL correlates with advantages of RT in DIBH, compared to FB-EH. For LL-tumours there is no difference between RT in FB-EH and RT in DIBH with respect to heart or lung exposure and therefore, reproducibility is the dominant criterion. FB-EH is recommended as a very robust and efficient technique for LL-tumours.